Un Royaume national des lettres - Inès Delpuech (Revue des Mondes Musulmans et de la Méditerranée)
Using three scales of variation – writers, association, and the State – this article examines the literary field in Jordan. Rooted in sociological history, it uncovers the ways through which cultural and literary nationalism has unfolded in Jordan since the 1970s onwards, identifying its supporting structures. In so doing, it shows how the contours of a specific Jordanian national culture took shape through the example of the Jordanian Writers’ Association (rābiṭat al-kuttāb al-urduniyyīn). By highlighting the plurality in interpretation of literary figures, the article also traces back the social experience of some writers in Jordan, through their own representations of what uncovers Jordanian literature.